Pendampingan Pemasaran Digital untuk Mendorong Sustainable Business pada Pelaku UMKM - Hendra Jonathan Sibarani; Yenni Yenni; Arifin Arifin; Errie Margery; Lusiah Lusiah; Ali Syah Putra; Sungguh Ponten Pranata; Fitria Halim; Sari Mariahma Nova Sipayung; Debora Tambunan (Institut Nalanda, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national economy, yet they often face challenges in maintaining business continuity (sustainability) in the digital era. This Community Service (PKM) program aims to provide digital marketing assistance to improve the competitiveness and sustainability of MSMEs. The methods used include needs analysis, interactive training (workshops), intensive coaching, and regular evaluations. The results of the program demonstrate a significant increase in partners' understanding of digital literacy, optimization of social media and marketplace usage, and increased sales turnover. This assistance has proven effective in building a sustainable business foundation through efficient marketing costs and expanding market reach, leading to a more stable market. Furthermore, MSMEs have demonstrated improved ability to create more engaging and professional promotional content and are beginning to manage their digital marketing strategies independently. This demonstrates that digital transformation impacts not only marketing but also the managerial capacity of entrepreneurs. Therefore, this mentoring program makes a real contribution to strengthening the sustainability of MSME businesses amidst increasingly competitive business conditions.